New Biofunctional Loading of Natural Antimicrobial Agent in Biodegradable Polymeric Films for Biomedical Applications - Ghafoor, Bakhtawar; Ali, Murtaza Najabat; Ansari, Umar; Bhatti, Muhammad Faraz; Mir, Mariam; Akhtar, Hafsah; Darakhshan, Fatima (International Journal of Biomaterials, 2016)
The study focuses on the development of novel Aloe vera based polymeric composite films and antimicrobial suture coatings. Polyvinyl alcohol (PVA), a synthetic biocompatible and biodegradable polymer, was combined with Aloe vera, a natural herb used for soothing burning effects and cosmetic purposes. The properties of these two materials were combined together to get additional benefits such as wound healing and prevention of surgical site infections. PVA and Aloe vera were mixed in a fixed quantity to produce polymer based films. The films were screened for antibacterial and antifungal activity against bacterial (E. coli, P. aeruginosa) and fungal strains (Aspergillus flavus and Aspergillus tubingensis) screened. Aloe vera based PVA films showed antimicrobial activity against all the strains; the lowest Aloe vera concentration (5%) showed the highest activity against all the strains. In vitro degradation and release profile of these films was also evaluated. The coating for sutures was prepared, in vitro antibacterial tests of these coated sutures were carried out, and later on in vivo studies of these coated sutures were also performed. The results showed that sutures coated with Aloe vera/PVA coating solution have antibacterial effects and thus have the potential to be used in the prevention of surgical site infections and Aloe vera/PVA based films have the potential to be used for wound healing purposes.